Experiments and Thermodynamic Modeling of Chukanovite (Fe2(OH)2CO3) to High Ionic Strengths. (20th March 2017) - Kim, Sungtae; Dean, Justin; Knox, Jandi; Kirkes, Leslie; Jang, Je-Hun
ABSTRACT: While conducting siderite (FeCO3 ) solubility experiments in NaCl-Na2 CO3 brines, evidence for a second phase was detected. Experiments, in which synthesized siderite was reacted with high ionic strength (0.18 – 7.5 m) solutions at room temperature and high pH (>10), were conducted in a glovebox. As the aging time of siderite-bearing experiments increased, the pH of the solution decreased, signaling formation of a hydroxyl-bearing phase. Decreasing pH values are interpreted to indicate that a hydroxyl-bearing phase, such as chukanovite, is the reaction controlling solid in the solid assemblage. Chukanovite was tentatively identified by XRD analysis. We set out, therefore, to determine the thermodynamic stability of chukanovite under the experimental conditions. Aqueous thermodynamic model parameters were determined with experimentally analyzed Fe(II) solubility data, and subsequently yielded a proposed formation free energy of chukanovite (-1149.8 kJ/mol).